2017
DOI: 10.1080/17453674.2017.1370845
|View full text |Cite
|
Sign up to set email alerts
|

Reduced length of uninterrupted institutional stay after implementing a fast-track protocol for primary total hip replacement

Abstract: Background and purposeFast-track protocols have been successfully implemented in many hospitals as they have been shown to result in shorter length of stay (LOS) without compromising results. We evaluated the effect of fast-track implementation on the use of institutional care and results after total hip replacement (THR).Patients and methods3,193 THRs performed in 4 hospitals between 2009–2010 and 2012–2013 were identified from the Finnish Hospital Discharge Register and the Finnish Arthroplasty Register. Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…Severe obesity (BMI >40) has effect on length of stay. All other grades of Obesity do not appear to affect the LOS; these results are consistent with other published literature [7][8][9][10][11][12][13][14] . When it comes to the implant choice, we have found that Uncemented THR has shorter length of stay as compared to Cemented total hip replacement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Severe obesity (BMI >40) has effect on length of stay. All other grades of Obesity do not appear to affect the LOS; these results are consistent with other published literature [7][8][9][10][11][12][13][14] . When it comes to the implant choice, we have found that Uncemented THR has shorter length of stay as compared to Cemented total hip replacement.…”
Section: Discussionsupporting
confidence: 91%
“…Enhanced recovery protocols have been implemented in many hospitals as they have been successful in achieving shorter LOS. A recently published study has concluded that reducing the LOS is achieved through such protocols but is also associated with increase in readmission rate and therefore needs careful implementation of such protocols to maintain good quality of care [9] . Number of procedures performed in any institution also affects length of stay.…”
Section: Introductionmentioning
confidence: 99%
“…However, several sources of literature show that the use of Fast-track protocols reduces the length of stay of patients. One recent study summarised information on 3000 patients in four Finnish hospitals and concluded that use of these protocols can reduce the length of stay from five to two days (Pamilo et al, 2018). Compared to Denmark, where fast-track protocols are used in very large number of hospitals, the average length of stay is 3.6 days (Anonymous, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be taken into account that the indicators from Finnish hospitals were better than the average in Latvia without the use of protocols. This can be explained by the fact that parts of these protocols, such as on patient education, limited use of drainage and urinary catheters have been introduced a long time ago (Pamilo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…he last decade has seen many areas of health care attempt to fast-track patient care. [1][2][3] In surgery, the focus is on enhancing recovery and reducing morbidity by implementing additions or changes, including perioperative pain management, patient education in preparation for surgery, early mobilization and aggressive postoperative fluid administration. [4][5][6][7] In orthopedics, shorter hospital stays have been shown to be safe and effective for selected groups of total joint arthroplasty patients.…”
mentioning
confidence: 99%